2016
DOI: 10.3389/fped.2016.00005
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Pediatric Critical Care in Resource-Limited Settings: A Look at Past, Present, and Future Directions

Abstract: Fifteen years ago, United Nations world leaders defined millenium development goal 4 (MDG 4): to reduce under-5-year mortality rates by two-thirds by the year 2015. Unfortunately, only 27 of 138 developing countries are expected to achieve MDG 4. The majority of childhood deaths in these settings result from reversible causes, and developing effective pediatric emergency and critical care services could substantially reduce this mortality. The Ebola outbreak highlighted the fragility of health care systems in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 115 publications
(139 reference statements)
0
67
0
4
Order By: Relevance
“…Educational interventions to build critical care capacity in resource-limited settings are important because of the underrepresentation of relevant topics in medical school curricula, the lack of post-graduate, critical care training pathways, and limited access to continuing medical education [66,67]. Interventions can range from short focused courses to longer-term programs based on academic partnerships between high-and low-income countries (including academic institutions, professional societies, and NGOs) that aim at training critical care specialists [66,67]. Short courses ( Table 1) cannot replace long-term clinical training but have the advantage of providing standardized education on specific topics to many clinicians, and can be implemented in response to acute needs.…”
Section: Education and Capacity Buildingmentioning
confidence: 99%
See 1 more Smart Citation
“…Educational interventions to build critical care capacity in resource-limited settings are important because of the underrepresentation of relevant topics in medical school curricula, the lack of post-graduate, critical care training pathways, and limited access to continuing medical education [66,67]. Interventions can range from short focused courses to longer-term programs based on academic partnerships between high-and low-income countries (including academic institutions, professional societies, and NGOs) that aim at training critical care specialists [66,67]. Short courses ( Table 1) cannot replace long-term clinical training but have the advantage of providing standardized education on specific topics to many clinicians, and can be implemented in response to acute needs.…”
Section: Education and Capacity Buildingmentioning
confidence: 99%
“…In contrast, longitudinal academic partnerships ( Table 2) can provide knowledge exchange platforms and build local ICU faculty expertise, but these depend on continuous on-site mentorship and training by visiting international faculty. Important factors for sustainability and avoidance of redundancy include integration with local medical education systems (pre-and post-graduate), alignment with priorities of local health authorities, development of academic partnerships in the country or region of interest [67], and adaptation to local cultural values [68,69]. In addition, it is essential to have a secure source of funding to ensure programmatic sustainability, retention of newly, highly trained faculty and continued expansion.…”
Section: Education and Capacity Buildingmentioning
confidence: 99%
“…57 One way of maximizing benefit would be to compare different health interventions and to selectively provide those that are most cost-effective. 59 The Burundi study of LBW infants found that over one quarter were lost to follow up, due to reasons including death, familial migration, and es- Prioritisation of children or young adults over preterm infants may lead to justice concerns. The feasibility of collecting neonatal health data in volatile, varied humanitarian disasters is questionable, with many current methods fraught with errors and limitations.…”
Section: Resource Allocationmentioning
confidence: 99%
“…15 This makes it difficult to properly classify and manage patients using scoring systems or guidelines largely obtained from the resource-rich settings. 16 Data on critical care capacity and access to both critical care resources and health care professionals are essential for health system planning. Published data on critical care research from resource-limited countries remain sparse, yet much needed.…”
Section: Introductionmentioning
confidence: 99%